SMARCC1 Suppresses Tumor Progression by Inhibiting the PI3K/AKT Signaling Pathway in Prostate Cancer - Xiao, Zhao-Ming; Lv, Dao-Jun; Yu, Yu-zhong; Wang, Chong; Xie, Tao; Wang, Tao; Song, Xian-Lu; Zhao, Shan-Chao (Frontiers in Cell and Developmental Biology, 2021)
ABSTRACT Background: SWI/SNF related, matrix associated, actin-dependent regulator of chromatin subfamily C member 1 (SMARCC1) protein is a potential tumor suppressor in various cancers. However, it’s role in prostate cancer (PCa) remains controversial. The aim of this study was to determine the biological function of SMARCC1 in PCa and explore the underlying regulatory mechanisms. Method: The expression of SMARCC1 was validated in PCa tissues by immunohistochemistry. Meanwhile, function experiments were used to evaluate the regulatory role on cell proliferation and metastasis in PCa cells with SMARCC1 depletion both in vitro and in vivo. The expression levels of relevant proteins were detected by Western blotting. Results: Our finding showed that SMARCC1 was significantly down-regulated in prostate adenocarcinoma with higher Gleason score (GS) than that in low GS. The decreased expression of SMARCC1 was significantly correlated with higher Gleason score and poor prognosis. Additionally, we found that silencing of SMARCC1 dramatically accelerated cell proliferation by promoting cell cycle progression and enhanced cell migration by inducing epithelial mesenchymal transition (EMT). Furthermore, depletion of SMARCC1 facilitated PCa xenograft growth and lung metastasis in murine models. Mechanistically, loss of SMARCC1 activated of the PI3K/AKT pathway in PCa cells. Conclusion: SMARCC1 suppresses PCa cell proliferation and metastasis via the PI3K/AKT signaling pathway, and is a novel therapeutic target.